PENGUKURAN TINGKAT KEMATANGAN TATA KELOLA TI BERDASARKAN 34 KERANGKA KERJA COBIT 4.1 - Irmawati Carolina (Swabumi, 2017)
Information Technology Support in business is very big because affects the continuity of operational processes of organizations. In its management, Information Technology needs a standard that can help managers to see the gaps between business risks, control needs, and problems. In its management, Information Technology needs a standard that can help managers to see the gaps between business risks, control needs, and problems of existing techniques. IT Governance is a structure of relationships and processes that drive and manage the organization in achieving its objectives by providing value-added of Informatiom Technology utilization and balancing risk with the results provided by Information Technology and processes. Maharaja Ban is a company that is committed to developing business and serving the needs of customers, so it needs the support of good IT Governance.  COBIT (Control Objectives for Information and Related Technology) is one tool in the measurement of IT Governance that is used to view existing IT governance. COBIT has 4 domains, namely Plan and Organization (PO), Acquisition and Implementation (AI), Delivery and Support (DS), and Monitoring and Evaluate (ME). This research was conducted for the fourth domain is the restriction on the 34 process . Research results found that the level of maturity (maturity level) IT Governance at Maharaja Ban on level 2. This means that the current maturity level was below the expected level of maturity, so it needs to be improved to be located at the expected level.